2020
DOI: 10.1371/journal.pbio.3001003
|View full text |Cite
|
Sign up to set email alerts
|

Self-limiting stem-cell niche signaling through degradation of a stem-cell receptor

Abstract: Stem-cell niche signaling is short-range in nature, such that only stem cells but not their differentiating progeny receive self-renewing signals. At the apical tip of the Drosophila testis, 8 to 10 germline stem cells (GSCs) surround the hub, a cluster of somatic cells that organize the stem-cell niche. We have previously shown that GSCs form microtubule-based nanotubes (MT-nanotubes) that project into the hub cells, serving as the platform for niche signal reception; this spatial arrangement ensures the rece… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 48 publications
6
16
0
Order By: Relevance
“…Therefore, we predicted that we would observe red and yellow puncta in control testes, but if autophagic flux is interrupted, the puncta will remain yellow. In control testes, GFP-negative and mCherry-positive Atg8a puncta were primarily observed in hub cells ( Fig 3E , hub delimited by dashed line), indicating that autophagasomes present in these somatic cells are able to acidify, in agreement with previous findings [54]. The rare Atg8a puncta observed in germ cells in control testes appeared yellow ( Fig 3E , arrowheads), suggesting that either these puncta correspond to autophagosomes that have not fused with lysosomes or that autolysosomes in wild-type germ cells do not properly acidify.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, we predicted that we would observe red and yellow puncta in control testes, but if autophagic flux is interrupted, the puncta will remain yellow. In control testes, GFP-negative and mCherry-positive Atg8a puncta were primarily observed in hub cells ( Fig 3E , hub delimited by dashed line), indicating that autophagasomes present in these somatic cells are able to acidify, in agreement with previous findings [54]. The rare Atg8a puncta observed in germ cells in control testes appeared yellow ( Fig 3E , arrowheads), suggesting that either these puncta correspond to autophagosomes that have not fused with lysosomes or that autolysosomes in wild-type germ cells do not properly acidify.…”
Section: Resultssupporting
confidence: 92%
“…In our previous study, we found that although Dpp ligand interacts with their receptor Dpp on the surface of MT-nanotubes 14 , we also noticed that Dpp ligand from the hub can diffuse farther away than previously thought 15 , indicating that Dpp ligand secreted from the niche provide both contact-dependent and contact-independent signal. Besides the apparent contact-dependent signaling role of Dpp in the niche, we wondered if the diffusing fraction of Dpp ligand plays any role in the cells located outside of the niche.…”
Section: Introductionmentioning
confidence: 61%
“…farther away than previously thought 15 , indicating that Dpp ligand secreted from the niche provide both contact-dependent and contact-independent signal. Besides the apparent contactdependent signaling role of Dpp in the niche, we wondered if the diffusing fraction of Dpp ligand plays any role in the cells located outside of the niche.…”
Section: Introductionmentioning
confidence: 80%
“…Self-renewal of hESCs has been demonstrated to rely on the feedback between endocytic pathways and E-cadherin-mediated adhesion [56] . In adult stem cells, trafficking of adhesion complex components to and from the cell surface is critical to ensure physical attachment to the niche which regulates stemness and differentiation [57] , [58] , [59] . Moreover, for cell migration, the assembly and disassembly of adhesive contacts by membrane trafficking is a prerequisite [60] .…”
Section: Bidirectional Effects Of Membrane Trafficking and Differenti...mentioning
confidence: 99%
“…In the Drosophila ovary, directional trafficking of adhesion proteins in germline stem cells enables only one daughter cell to adhere to the niche cells while the other differentiates subsequently [57] . In the Drosophila testis, targeted receptor trafficking to specialized contact sites between the stem cell and the niche cells (microtubule-containing nanotubes) limits signaling spatially to these cells [58] . These examples illustrate the importance of the positional information conveyed through directional trafficking to maintain stemness and to organize differentiation of daughter cells.…”
Section: Bidirectional Effects Of Membrane Trafficking and Differenti...mentioning
confidence: 99%